Content and Language Integrated Learning (CLIL) Implementation for Indonesian EFL Learners: A Case Study - Norhasanah; Rozi Setiawan (SAGA: Journal of English Language Teaching and Applied Linguistics, 2023)
This paper aims to investigate CLIL implementation for English teaching in Indonesia, particularly how this approach can be used in the EFL learning context considering that in most cases CLIL is implemented for bilingual education. To get the information and learn the phenomena in depth, a study case was conducted. The data was collected through classroom observation of two English teachers who have implemented CLIL in their teaching practice. It was then followed by a focus group discussion with those teachers to confirm the CLIL application and get more comprehensive data. This study found that CLIL was quite significant to be implemented for teaching English as it was not only able to improve students’ language skills but also broaden their insight globally. From this study, it was also highlighted that teachers must carefully select the materials and consider students’ level of proficiency to make a meaningful and effective learning process.